2011
DOI: 10.1016/j.ridd.2010.10.014
|View full text |Cite
|
Sign up to set email alerts
|

Route learning and shortcut performance in adults with intellectual disability: A study with virtual environments

Abstract: The ability to learn routes though a virtual environment (VE) and to make novel shortcut between two locations were assessed in eighteen adults with intellecual disability and eighteen adults without intellectual disability matched on chronological age. Participants explored two routes (AB and AC) until they reached the learning criterion. Then, they were placed in B and were asked to find the shortest way to C (BC, five trials). Participants in both groups could learn the routes, but most of the participan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 50 publications
(28 citation statements)
references
References 22 publications
2
21
0
5
Order By: Relevance
“…Survey knowledge provided by both slanted and survey perspectives may include relational information about landmarks or road segments between which direct travel has never occurred. The ability to find novel shortcuts between two points is considered to be characteristic of survey knowledge [1], [33][35] and the difficulty of finding a shortcut after a route-perspective encoding might be interpreted as reflecting the difficulty of developing an effective strategy to find shortcuts using only coarse and possibly nonmetric spatial knowledge derived from route-perspective encoding.…”
Section: Discussionmentioning
confidence: 99%
“…Survey knowledge provided by both slanted and survey perspectives may include relational information about landmarks or road segments between which direct travel has never occurred. The ability to find novel shortcuts between two points is considered to be characteristic of survey knowledge [1], [33][35] and the difficulty of finding a shortcut after a route-perspective encoding might be interpreted as reflecting the difficulty of developing an effective strategy to find shortcuts using only coarse and possibly nonmetric spatial knowledge derived from route-perspective encoding.…”
Section: Discussionmentioning
confidence: 99%
“…Mengue-Topio et al [5] experimented with virtual environments to assess the ability of route learning, and being able to make shortcuts between two locations was carried on 18 adults with ID and 18 adults without disabilities. This experiment comprised of the exploration of two routes until each adult reached a learning criterion.…”
Section: Related Workmentioning
confidence: 99%
“…Reduced opportunities for independent navigation and active exploration in real‐world environments may inhibit individuals with physical disabilities from acquiring allocentric knowledge (Foreman, ; Foreman, Stanton, Wilson & Duffy, ). Findings have suggested that this may also be the case for individuals with learning difficulties (Farran et al ., ; Mengue‐Topio, Courbois, Farran & Sockeel, ). Given the time restraints and physical demands involved in navigating a route multiple times, real‐world tasks in WS may be limited by the scope of experience that each participant can gain from an environment.…”
Section: Introductionmentioning
confidence: 99%